OPTIMALISASI pH PRODUKSI SELULASE DARI BAKTERI ENDOFITIK Pseudomonas stutzeri LBKURCC53, Pseudomonas stutzeri LBKURCC54, dan Actinobacter antratus LBKURCC60 - Rizki Wulandari; Silvera Devi; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Cellulase is an enzyme that can hydrolyze the β-1,4 bonds on cellulose and productionof glucose so that the enzyme is widely used in various industries. Cellulose enzymes can be produced by microorganism such as endophytic bacteria (LBKURCC53, LBKURCC54, and LBKURCC60). The activity of cellulase enzyme was determined by measuring the glucose produced using Nelson-Somogyi method. The optimum activity of cellulase enzyme from theisolates of LBKURCC53, LBKURCC54, and LBKURCC60 we measured at different pH. The enzyme of LBKURCC53 isolate was optimum at pH 7 with enzyme activity of 11,31 ± 1,69 x 10 -3 U/mL. While the enzyme of LBKURCC54 and LBKURCC60 isolates were optimum at pH 6,5 with enzyme activity 14,44 ± 2,94 x 10 -3 U/mL and 8,33 ± 1,11 x 10 -3 U/mL respectively. These comparison of cellulase enzyme activity of isolates LBKURCC53, LBKURCC54, and LBKURCC60 were determined by using Duncan multiple range test at 5% level (α≥0,05).